2008
DOI: 10.1261/rna.1125408
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic rearrangements of a mycoreovirus induced by the multifunctional protein p29 encoded by the prototypic hypovirus CHV1-EP713

Abstract: Mycoreovirus 1 (MyRV1), a member of the Reoviridae family possessing a genome consisting of 11 dsRNA segments (S1-S11), and the prototype hypovirus (CHV1-EP713) of the Hypoviridae family, which is closely related to the monopartite picorna-like superfamily with a ssRNA genome, infect the chestnut blight fungus and cause virulence attenuation and distinct phenotypic alterations in the host. Here, we present evidence for reproducible induction of intragenic rearrangements of MyRV1 S6 and S10, mediated by the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 51 publications
6
76
1
Order By: Relevance
“…Because the 5= UTRs of hypoviruses often are highly structured, it is possible that stem-and-loop structures in this region facilitated the shift of viral replicase from the RNA of one progenitor virus species to the other during virus replication. Both host and virus factors have been shown to be involved in RNA-RNA recombination of hypoviruses in C. parasitica, including a host Argonaute enzyme and viral RNA silencing suppressor (RSS) (72,73). Additional studies are needed to evaluate the roles of secondary structures in the 5= UTR of SsHV2 in translation initiation and recombination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the 5= UTRs of hypoviruses often are highly structured, it is possible that stem-and-loop structures in this region facilitated the shift of viral replicase from the RNA of one progenitor virus species to the other during virus replication. Both host and virus factors have been shown to be involved in RNA-RNA recombination of hypoviruses in C. parasitica, including a host Argonaute enzyme and viral RNA silencing suppressor (RSS) (72,73). Additional studies are needed to evaluate the roles of secondary structures in the 5= UTR of SsHV2 in translation initiation and recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are needed to identify the RSS expressed by SsHV2 and investigate its potential role in suppression of pigmentation and sclerotium production. Identification of the RSS could lead to a further understanding of how RNA mycoviruses disrupt the antiviral defenses of their fungal hosts and effects on host gene expression that lead to alterations in fungal growth, morphology, and virulence (73,81).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these hypoviral DIRNAs affect viral replication and the fungal host phenotype is unknown. DI segments S4ss and S10ss (rearranged dsRNA segments) of a mycoreovirus, Mycoreovirus 1 (MyRV1), have been shown to contribute to altered symptom induction (12,13,43). DI segments were also identified in Saccharomyces cerevisiae infected with dsRNA viruses (totiviruses, family Totiviridae) that were derived from a satellite RNA (called M dsRNA) (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some members additionally harbor satellitelike dsRNA segments either carrying or lacking a potential open reading frame (ORF) (11). However, unlike other dsRNA viruses, such as mycoreovirus (genus Mycoreovirus), for which DI-RNAs have been reported (12,13), partitiviruses have never been reported to carry DI-RNA species accompanied by a helper virus. Because of the unavailability of reverse genetics for, and the artificial introduction of, most partitiviruses, no clear picture of interactions among subviral RNAs, their helper viruses, and hosts has emerged.…”
mentioning
confidence: 99%
“…3C and D). (51), and H. victoriae A-9 (genome of a victorivirus and a chrysovirus) (62) were analyzed comparatively by 1.0% agarose gel electrophoresis (78). The mobilities of dsRNAs are specified to the left of the panel, respectively.…”
Section: W1029 Is Infected With a Novel Partitivirus And A Novel Victmentioning
confidence: 99%